Pembelajaran Bahasa Inggris Menggunakan Media LaguPada Sekolah Berbasis Budaya LokalDi SMK Negeri 8 Surakarta - Sulistianingtyas, Budianti, Prof. Dr. Ali Imron Al-Ma'ruf, M.Hum, Dr. Phil Dewi Candraningrum (2015)
The purpose of this study was to describe (1) planning; (2) implementation; (3) obstacles; and (4) solutions in learning English using Songs on local culture based school at SMKN 8 Surakarta The research is a qualitative research. The data obtained is field note and pictures. The sources of the data is teacher administration document, interviwees, and it takes place in SMKN 8 Surakarta. The technique of collecting data through observation, interviews and documentation. The results showed that (1) The planning in learning English using songs on local culture based school at SMKN 8 Surakarta was done by preparing a teacher administration in the form of lesson plans, materials, methods, space and instructional media. (2) The implementation in learning English usings songs on local culture based school in SMKN 8 Surakarta was active and occurs from various directions. Interaction occurs between teachers and students and between students and other students. The class activity started by greeting, praying and continuing with apperception. Core activities are focused on five (5) it is observing activity, questioning, identifying, associating and communicating a masterpiece. At the end of the activities carried out by giving a conclusion followed by a closing prayer and greetings. (3) The obstacles in learning English using songs on local culture based school at SMKN 8 Surakarta were not on schedule lesson planning, the in attractive song material, rooms and media were less supportive. (4) The solution in learning English using songs on local culture based school in SMKN 8 Surakarta were using the next meeting to discuss the left behind material, looking for and discussing the interesting material, facilitating by own teacher in using media.